Pengaruh Kepuasan, Kedisiplinan, dan Motivasi Kerja terhadap Kinerja Awak Kapal PT. Timur Ship Manajement Jakarta - Ardo Ardian; Dimas Ilham Putranto; Erie Cantona (Universitas Batanghari, 2023)
In general, this study aims to gain an overview of the performance crew of PT Timur Ship Management Jakarta through job satisfaction, discipline, and motivation. The method used is explanatory research with quantitative approach. The population is ship crew of PT Timur Ship Management Jakarta as many as 52. Meanwhile, in the selection of the sample, the researchers used sampling saturated, because the population is limited and less than 100, then the number of samples in this study as many as 52 respondents. Data collection techniques include literature study obtained by studying reference books and a number of other literature, as well as distributing questionnaires to the respondents who selected and collecting documentation. Furthermore, the techniques of data analysis is a method of multiple linear regression with SPSS 17.00. The results showed that job satisfaction, work discipline, and motivation to work partially and simultaneously have a positive significant effect on the performance of the crew of PT. Timur Ship Management Jakarta. The magnitude of the effect of job satisfaction, work discipline, and motivation to work simultaneously on the performance of the crew of 88.90%, and it is known that job satisfaction is the most dominant factor shaping the performance of the crew with the amount of 0.918 correlation indicates a very strong relationship.